A Bibliometric Approach to Assessing the Potential Research on the Use of Virtual Classroom in Vocational Education - Riyanto, Sugeng Dwi; Pratiwi, Artdhita Fajar; Ilahi, Novita Asma; Rafiq, Arif Ainur (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
Education is progressing faster than at any other time in history. Educators are becoming increasingly conscious that today's learning media are developing to match future realities. Education must establish new approaches in the learning process by employing virtual classrooms and tools and technology. The virtual classroom concept offers a solution for today's and tomorrow's educational needs. To prepare for future employment, students require a holistic education that combines practical occupational skills, communication methods, and leadership development. This paper will give a bibliometric analysis of the term virtual classroom as a learning media, focusing on future research trends in vocational education. The articles were obtained with the help of the Publish or Perish software and the Scopus database. With a search period spanning 2013 to 2022, 405 articles were evaluated (9 years period). The desktop version of the Mendeley program is used to handle the references. VOS Viewer software was used to classify the articles by generating six clusters. The main keywords from the six groupings are virtual reality, e-learning, teaching, education, augmented reality, and improved classroom instruction.